Consolidated Assessment of UPK Revolving Loan Funds in Indonesia for their Financial Performance and Capacity Building Needs - World Bank (Washington, DC, 2015)
This is the final consolidated report of an extensive program to assess the financial performance and capacity building needs of the UPK Revolving Loan Funds under the PNPM Mandiri project. As explained in the report, the assessment program covered 508 rural and urban UPKs in the provinces of Central Java, Yogyakarta, Nusa Tenggara Timor and West Sumatra. The aim was to cover 30 percent of rural UPK RLFs in these four provinces and 10 percent of the urban UPKs in order to establish the achievements and determine areas of improvement to enable these UPKs to provide a better service to the low income families in their operational areas. This report covers all 267 rural UPK RLFs and 241 urban UPKs identified for the purpose in the four provinces.